Clinical pathology and radiological assesment of feline chronic gingivostomatitis - Hussain, Haidary Mohammad (2020)
Feline chronic gingivostomatitis (FCGS) is a severe inflammatory oral disease of cats that often refractory to treatment. The etiology is unknown but it has been attributed to bacterial agents, viral agents, and immunologic factors. The association of FCGS to dentoalveolar lesions is poorly defined. This study presents the clinical, pathological, immunofluorescence, and computed tomographic findings of 15 cats with FCGS and 7 without FCGS. Clinical examination of the oral cavity was performed and oral pathological lesions were recorded. Blood, oral swab, and excisional biopsy from palatoglossal fold were collected under general anesthesia. Histopathological analysis and immunofluorescence staining for immune cells, CD4 and CD8 were performed on the oral tissue biopsies. The swab samples were analyzed for the presence of Bartonella henselae and Pasteurella multocida using PCR and bacteria culture, respectively. Blood was subjected to hematological and biochemical analysis and screened for feline calicivirus (FCV), feline herpesvirus (FHV), feline immunodeficiency virus (FIV), and feline leukemia virus (FeLV). Computed tomography (CT scan) was performed to elaborate on the dentoalveolar lesions. The main clinical findings were halitosis (73.3%), Anorexia (60%), dysphagia (53.3%), bleeding gum (33.3%), weight loss (26.7%), and ptyalism (20%). CT scan revealed different types of dentoalveolar lesions where furcation (73.3%), edentulous (66.6%), horizontal bone loss (66.6%), dental resorption (53.3%), vertical bone loss (40%), fracture (33.3%), and impacted tooth (13.3%). Viral screening was positive for FCV (86.6%), FHV (73.3%), FIV (22.2%) and FeLV (5.6%). The blood and oral swabs were negative for Bartonella henselae. Histopathologically, the excisional biopsies were characterized by the infiltration of inflammatory cells in the epithelium and lamina propria. It is worthy to note that, the present study reveals that, viruses like FCV, FHV, and FIV contribute greatly to the cause of FCGS and the study also discovered that, FCGS is associated with various types of dentoalveolar lesions.